Flexible Metal–Organic Frameworks as CO2 Adsorbents en Route to Energy‐Efficient Carbon Capture. Issue 5 (12th May 2022) - Yao, Xuan; Cordova, Kyle E.; Zhang, Yue-Biao
Abstract : Flexible Metal‐Organic Frameworks Metal‐organic frameworks (MOFs) have been proposed as outstanding solid adsorbents for carbon capture. Especially, flexible MOFs hold promise for high energy efficiency by balancing high working capacity, high selectivity, and low regeneration energy. In article number 2100209, Yue‐Biao Zhang and co‐workers review the carbon capture performances of flexible MOFs and introduce the stimulating works heading for practical applications.